Evaluasi Disiplin ASN Berdasarkan Perwali Kota Surabaya Nomor 44 Tahun 2022 - Meissa Fahdilla Yodha Pramita; Nevada Salsabillah; Fadila Andini Syahputri; Wildan Taufik Raharja (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2026)
This study aims to evaluate the implementation of civil servant discipline enforcement based on Surabaya Mayor Regulation Number 44 of 2022 at Gubeng Subdistrict. The research employs a qualitative approach with a case study design. Data were collected through in-depth interviews, observation, and document analysis, and analyzed using the interactive model of Miles and Huberman within the Context–Mechanism–Outcome (CMO) framework. The findings indicate that the regulation has generally improved civil servant discipline, particularly in attendance, punctuality, administrative compliance, and public service quality. This improvement is supported by organizational context factors such as daily work culture, active leadership, and the integration of digital attendance systems. Key mechanisms driving compliance include layered supervision, persuasive coaching, and the gradual application of disciplinary sanctions. However, challenges remain, including high workloads and limited human resources, which require continuous guidance for certain employees. The study concludes that the effectiveness of civil servant discipline enforcement is largely shaped by the interaction between organizational context and policy implementation mechanisms.